2015
DOI: 10.1016/j.molcata.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-promoted coupling of arylboronic acids with olefins catalyzed by [CA]2[PdX4] complexes without a base

Abstract: a b s t r a c tAn efficient method was developed for the oxidative Heck reaction between arylboronic acids and olefins catalyzed by anionic palladium complexes of the type [CA] x [PdCl 4 ] (x = 1,2) and [CA] 2 [Pd 2 Cl 6 ] (CA = imidazolium or pyridinium cation). Molecular oxygen was employed as an environmentally benign oxidant to regenerate Pd(II) species during the reaction. The elaborated protocol could be applied to the coupling of different arylboronic acids with both electron-rich and electron-poor olef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Our approach, presented in this paper, was based on a tandem process involving two arylation steps with the same catalyst, without the isolation of the first aryl ketone (Figure ). The second modification consisted in the application of MW irradiation instead of conventional heating . It was expected that this would shorten the reaction time and save energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach, presented in this paper, was based on a tandem process involving two arylation steps with the same catalyst, without the isolation of the first aryl ketone (Figure ). The second modification consisted in the application of MW irradiation instead of conventional heating . It was expected that this would shorten the reaction time and save energy.…”
Section: Introductionmentioning
confidence: 99%
“…The second modification consisted in the application of MW irradiation instead of conventional heating. [12,[45][46][47] It was expected that this would shorten the reaction time and save energy.…”
Section: Introductionmentioning
confidence: 99%
“…In situ ESI‐MS experiments showed evidence of [(IL) x Pd 3 ] cluster formation if complexes of the type [IL] 2 [PdX 4 ] were used as catalyst precursors . Other anionic Pd complexes of the type [IL] 2 [PdX 4 ] have been reported and used as pre‐catalysts in the Suzuki–Miyaura reaction, in the oxidative Heck reaction and other catalytic applications . Recently, inorganic–organic hybrid materials have attracted great interest thanks to their excellent performance in terms of thermal and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…We performed an in-depth analysis of the reasons for the high catalytic activity, which explained the higher activity of 1a compared with 1b and 1c and suggested that complex 1a might also be suitable for other cross-coupling reactions. Earlier results by Dyson , and Trzeciak, among others, on related anionic palladium complexes support this suggestion (Scheme d).…”
Section: Introductionmentioning
confidence: 65%